Spatial Distribution of Heavy Metals in the Farmland at the Confluence of Songhua and Heilong Rivers, China - Niu, J.T.; Wang, Q.H.; Guo, Q.K.; Li, Y.; Li, F.S. (Asian Journal of Chemistry, 2013)
Sanjiang plain, which is an alluvial land situated at the confluence of Songhua, Heilong and Ussuri Rivers in northeast of China, is an important commodity grain base. Within the confluence zone, the contents of five heavy metals (Cd, Hg, As, Pb and Cr) in surface soils were sampled and monitored in 21 villages around Tongjiang, Fujin and Suibin Cities. Spatial distribution analysis and assessment were conducted by using GIS technology, Müller geoaccumulation index and Håkanson potential ecological risk index. Heavy metal contents in the studied area range as follows: Cd, 0.048-0.280 mg/kg; Hg, 0.017-0.079 mg/kg; As, 4.73-18.16 mg/kg; Pb, 15.9-34.8 mg/kg and Cr, 16.8-55.1 mg/kg, indicating that the detection results meet the agricultural industry standard of China, i.e., environmental condition standards for pollution-free food production (NY5332-2006). Statistical analysis showed that there are certain correlations among Cd, As and Pb. In Fujing City, the southwest region of the studied area, Cd, As and Pb levels are elevated. Hg distribution is dispersed and Cr level is elevated in the eastern and southern parts of the studied area. Moreover, the calculations of Müller geoaccumulation index and Håkanson potential ecological risk index indicate that light pollution is caused by Cd and As and that the majority of the studied area is exposed to slight ecological risk.